Pengembangan Bahan Ajar Digital Berbasis Flipbook pada Mata Kuliah Pancasila Prodi Penjaskesrek Universitas PGRI Mahadewa Indonesia - Sudiarta, I Gusti Ngurah; Tara, Made Nohan; Widhiyanti, Komang Ayu Tri; Ariawati, Ni Wayan (MAN Insan Cendekia Jambi, 2025)
This study focuses on the development of digital teaching materials in a flipbook format for the Pancasila course, targeting first-semester students of the Department of Physical Education, Health, and Recreation (Penjaskesrek) at Universitas PGRI Mahadewa Indonesia for the 2025/2026 Academic Year. This innovation was undertaken to address the need for learning resources that are interactive, engaging, and relevant to the 21st-century context. Utilizing the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate), the resulting product underwent rigorous validation. The validation results demonstrated a highly feasible level, with scores of 92% from content experts, 90% from media experts, and 91% from student response trials. These findings indicate that the flipbook is highly effective as a learning medium, receiving positive feedback for its ease of navigation and visual integration, while successfully enhancing student motivation and active participation in comprehending Pancasila values.